Spatial organization for rational land use and environmental protection in Uong Bi Town by functional sub-areas - Truong, Quang Hai (VNU, 2014)
Spatial or territorial organization is one of effective tools for sustainable land use. Spatial organization of land use and environmental protection by functional sub-areas is performed on the basis of comprehensive and integrated research on characteristics and differentiation laws of natural components and landscapes, socio-economic factors, the present status and trend of environmental changes as well as the structures andfunctions of sub-areas. Uong Bi is a national center for tourism, coal mining and thermal power production. The development of economic sectors has led to a seriesof urgent environmental and social problems, requiring implementation of plans and solutions forensuring sustainable development. This paper proposes a scientific-based spatial organization ofland use and environmental protection by eight functional sub-areas in the Uong Bi Town area.